2007
DOI: 10.1016/j.jcrs.2006.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Suture-related complications after congenital cataract surgery: Vicryl versus Mersilene sutures

Abstract: Vicryl sutures are recommended for small-incision congenital cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In addition to causing a foreign-body sensation, sutures may induce astigmatism 1,2 and corneal neovascularization 3 or be a nidus for infection. 1,4,5 Unless biodegradable materials are used, the sutures must be removed. For these reasons, we believe that an ophthalmic tissue adhesive with specific characteristics aimed at the needs of common ophthalmic surgical procedures would have clinical value.…”
mentioning
confidence: 99%
“…In addition to causing a foreign-body sensation, sutures may induce astigmatism 1,2 and corneal neovascularization 3 or be a nidus for infection. 1,4,5 Unless biodegradable materials are used, the sutures must be removed. For these reasons, we believe that an ophthalmic tissue adhesive with specific characteristics aimed at the needs of common ophthalmic surgical procedures would have clinical value.…”
mentioning
confidence: 99%
“…Small, unsutured clear corneal incisions are preferred by many cataract surgeons in the setting of phacoemulsification. If a no-suture technique is used, meticulous wound construction must be pursued to achieve a watertight wound with no gaping 24,25. However, an increased incidence of endophthalmitis has been associated with sutureless closures 24-26.…”
Section: Discussionmentioning
confidence: 99%
“…If a no-suture technique is used, meticulous wound construction must be pursued to achieve a watertight wound with no gaping 24,25. However, an increased incidence of endophthalmitis has been associated with sutureless closures 24-26. Some studies have strongly suggested that optimal protection against endophthalmitis is achieved when the wound is closed with a suture 25.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the use of 10-0 Vicryl caused astigmatism, but that this astigmatism dissipated after 6 weeks. 108 …”
Section: Surgical Techniquementioning
confidence: 99%